The mechanisms of up‐regulation of dendritic cell activity by oxidative stress. Issue 2 (27th March 2014) - Batal, Ibrahim; Azzi, Jamil; Mounayar, Marwan; Abdoli, Rozita; Moore, Robert; Lee, Jack Y.; Rosetti, Florencia; Wang, Chang; Fiorina, Paolo; Sackstein, Robert; Ichimura, Takaharu; Abdi, Reza
Abstract : Oxidative stress enhances dendritic cellsˈ capability of inducing CD4 + T cell proliferation and production of proinflammatory cytokines and PI3Kγ‐dependent migration, but reduces generation of T‐regulatory cells. Abstract : Whereas DC have increasingly been recognized for their role in activating the inflammatory cascades during IRIs, the mechanisms by which oxidative stress enhances DC activation remain to be explored. We examined the role of oxidative stress on two important features of DC: T cell activation and trafficking. Bone marrow‐derived OS‐DC were compared with untreated DC. DC exposed to oxidative stress augmented allogeneic T cell proliferation and showed increased migration in a chemotaxis chamber. These results were confirmed by using hypoxanthine and xanthine oxidase as another inducer of oxidative stress. We used OT‐II and OT‐I mice to assess the effect of oxidative stress on DC activation of OVA‐specific CD4 + and CD8 + T cells, respectively. Oxidative stress increased DC capacity to promote OVA‐specific CD4 + T cell activity, demonstrated by an increase in their proliferation and production of IFN‐γ, IL‐6, and IL‐2 proinflammatory cytokines. Whereas oxidative stress increased the DC ability to stimulate IFN‐γ production by OVA‐specific CD8 + T cells, cellular proliferation and cytotoxicity were not affected. Compared with untreated DC, oxidative stress significantly reduced the capacity of DC to generate Tregs, which were restored by using anti‐IL‐6. With regard to DC trafficking, whereas oxidative stress increased DC expression of p‐Akt and p‐NF‐κB, targeting PI3Kγ and NF‐κB pathways abrogated the observed increase in DC migration. Our data propose novel insights on the activation of DC by oxidative stress and provide rationales for targeted therapies, which can potentially attenuate IRI.